IMPOSITION ON REAL ESTATE PROPERTY UNDER THE CONDITIONS OF ADMINISTRATIVE-TERRITORIAL DECENTRELIZATION AND OF THE INCREASE OF FINANCIAL SELF-GOVERNMENT OF LOCAL COMMUNITIES - GHEORGHE MATEI; OLIVIA BURCEA (MANOLE) (Annals of the University of Petrosani: Economics, 2011)
In all the countries with a consolidated and developed democracy from the economic point of view, a major part of public affairs are assigned in the administrativefinancial and regulatory responsibility of local authorities. Similar to other states, in Romania this process of decentralization, due to its inter-sector characteristic, is also of a distinctive complexity, imposing clear and efficient regulations, together with the implementation of a performant management at the level of all the involved actors, including that of the recipients. The fulfillment of this process supposes at the same time a financial support in accordance with the assigned responsibilities. The article presents several practical consolidation modalities of the financial resources of the local communities obtained from own incomes. Thus, the realization of a corresponding equilibrium between the tasks transferred from the central level and the real financing possibilities existent at the local level, is considered.